Nurses’ Compliance about Patient Safety in Improving Drug Safety as an Effort to Reduce Medication Error: A Literature Review - Christina Anugrahini; Rr. Tutik Sri Hariyati (Indonesian Journal of Global Health Research, 2020)
Patient safety is a patient who is free from injuries that do not occur or free from damage and/or potential illness, physical, social, psychological, disability, and death related to health care. Nurse compliance is compliance to an action, procedure or regulation that must be done or obeyed. The purpose of this paper was to know the Nurses’ Compliance towards Patient Safety in improving Drug Safety as an Effort to Reduce Drug Errors. The method of this research was a literature review design. The literature search process used several databases including ProQuest, Ebsco, and the Willey Online Library. The search was done on literatures published between 2013 and 2018. Keywords included were keywords relevant to the material, including “nurse compliance - drug safety - drug error - nurse medication error”. The data analysis used a specific conceptual approach which analyzed an outline to achieve objectives using PRISMA. Sixth articles fullfilled the inclusion criteria. This study found various research articles under discussion that the nurses’ compliance about patient safety in improving drug safety as an effort to reduce medication errors is to report patient safety incidents, near injury, potential incidence of injury, non-injured incident and unexpected events. Provision of trainings and updating knowledge about patient safety in terms of reducing medication errors are needed. In addition, compliance to report if there is a patient safety incident also needs to be improved, because the report can be an early response to patient safety incidents in the future which can prevent the same incident to happen again.